Citrus Greening and Citrus Tree Planting in Florida - Thomas H. Spreen; Jean-Paul Baldwin (EDIS)
This 4-page fact sheet examines the impact of the presence of citrus greening on new tree plantings in the Florida citrus industry. Sweet oranges are by far the most important citrus variety grown in Florida, so the analysis is limited to sweet orange plantings. Because citrus greening impacts citrus producers through reduced yield, increased mortality, and increased cost of production, it is expected that the presence of citrus greening has had an adverse impact on the willingness of growers to invest in new trees. Written by Thomas H. Spreen and Jean-Paul Baldwin, and published by the UF Department of Food and Resource Economics, January 2014.